2005
DOI: 10.1111/j.1399-3011.2004.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization of several linear penta‐ and heptapeptides with different metal ions studied by CD spectroscopy*

Abstract: A cyclic pentapeptide c(Tyr-Leu-Ala-Gly-Pro) (I), which was isolated and identified from Pseudostellaria heterophylla medicinal herbs, and two cyclic heptapeptides, c(Gly-Tyr-Gly-Gly-Pro-Phe-Pro) (II) and c(Gly-Ile-Pro-Tyr-Ile-Ala-Ala) (III), which were isolated and identified from Stellaria yunnanensis Franch (M), were synthesized by using 3-(diethoxyphosphoryloxy)-1,2,3-benzotriazin-4(3 H)-one (DEPBT) as a coupling reagent in solution, and mediated by different metal ions, from their linear peptide precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
0
20
1
Order By: Relevance
“…Although this route constituted a synthesis of verticilide in six steps with 8% overall yield, an improved yield of verticilide by MCO was sought based on the hypothesis that the growing oligomers might bind to salt additives (16,17,(36)(37)(38)(39)(40)(41), which in turn, might lead to depsipeptide-salt complexes with a conformationally enhanced rate of macrocyclization relative to chain elongation. Known applications of this phenomenon to depsipeptide macrocycle synthesis are macrolactamization (38,39) reactions, which are conducted in a polar solvent that can readily solubilize the salt additive.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Although this route constituted a synthesis of verticilide in six steps with 8% overall yield, an improved yield of verticilide by MCO was sought based on the hypothesis that the growing oligomers might bind to salt additives (16,17,(36)(37)(38)(39)(40)(41), which in turn, might lead to depsipeptide-salt complexes with a conformationally enhanced rate of macrocyclization relative to chain elongation. Known applications of this phenomenon to depsipeptide macrocycle synthesis are macrolactamization (38,39) reactions, which are conducted in a polar solvent that can readily solubilize the salt additive.…”
Section: Significancementioning
confidence: 99%
“…Known applications of this phenomenon to depsipeptide macrocycle synthesis are macrolactamization (38,39) reactions, which are conducted in a polar solvent that can readily solubilize the salt additive. However, the use of polar solvents and salt additives is contraindicated in a Mitsunobu reaction because of their ability to disrupt the reactive ion pairs (42)(43)(44), potentially slowing or stopping the coupling reaction entirely.…”
Section: Significancementioning
confidence: 99%
“…The formulas of eight cyclic pentapeptides7, 8 are shown in Scheme . Boc: tert ‐butyloxylcarbonyl; Aph: β‐(aminophenyl)‐alanine; Nal: β‐naphthyl‐alanine; Pal: β‐(3‐pyridyl)‐alanine; Phg: phenylglycine.…”
Section: Methodsmentioning
confidence: 99%
“…However in a LiCl/dimethyl formamide solvent mixture, exclusive monomeric cyclization was observed through a nucleophilic displacement of the N-terminal chloroacetyl moiety by the C-terminal cysteine thiol. Ye and co-workers have shown that sodium ions are suitable for promoting the cyclization of linear pentapeptides, whereas larger caesium ions can effectively promote the cyclization of heptapeptides 54,55 . Supported by molecular mechanics calculations, Ye and co-authors propose that these alkali metal ions promote peptide macrocyclization by initially binding the carbonyl and amide groups at the C-terminus of a peptide.…”
Section: Metal-ion-assisted Cyclizationsmentioning
confidence: 98%